Aplikasi Monitoring Detak Jantung Menggunakan Sensor Max30102 dan Algoritma Gaussian Naive Bayes - Beni Mustiko Aji; Wahyu Sri Utami (JURNAL PERANGKAT LUNAK, 2023)
Heart health is important as it is the leading cause of death in Indonesia, especially among the elderly. However, the elderly is not routinely monitored because the Integrated Health Post Ngudi Makmur does not have access to heart rate checks. The author suggests a solution to this problem, namely a heart rate monitoring application with a max30102 sensor to monitor heart rate using the gaussian naive bayes algorithm which is expected to be able to help check heart rate in the elderly at Integrated Health Post Ngudi Makmur. This application allows continuous monitoring of heart rate. To ensure a smooth development process, black box testing techniques are used for functional testing of the application. Functionally, this application has been in accordance with the expectations of the author. In addition, the authors developed a device to measure heart rate using a max30102 sensor. An accuracy of 95.8% was found in the calibration results of the device used, while testing the gaussian naive bayes algorithm using the k-fold cross validation method showed an accuracy of 91%. It is hoped that the elderly at Integrated Health Post Ngudi Makmur can more regularly check their heart health.